Bribery in health care in Peru and Uganda - Jennifer Hunt (Institute for the Study of Labor (IZA), 2007)
In this paper, I examine the role of household income in determining who bribes and how much they bribe in health care in Peru and Uganda. I find that rich patients are more likely than other patients to bribe in public health care: doubling household consumption increases the bribery probability by 0.2-0.4 percentage points in Peru, compared to a bribery rate of 0.8%; doubling household expenditure in Uganda increases the bribery probability by 1.2 percentage points compared to a bribery rate of 17%. The income elasticity of the bribe amount cannot be precisely estimated in Peru, but is about 0.37 in Uganda. Bribes in the Ugandan public sector appear to be fees-for-service extorted from the richer patients amongst those exempted by government policy from paying the official fees. Bribes in the private sector appear to be flat-rate fees paid by patients who do not pay official fees. I do not find evidence that the public health care sector in either Peru or Uganda is able to price-discriminate less effectively than public institutions with less competition from the private sector.
urn:nbn:de:101:1-20080402177
Keywords: 330; Gesundheitswesen; Korruption; Uganda; Peru